Presence of adult Loa loa in the anterior chamber of the eye along with microfilaremia from nonendemic region: A rare presentation from India - Varsha Kumari; Sofia Ahmad; Aradhana Singh; Tuhina Banerjee (Tzu Chi Medical Journal)
We report an unusual case of adult Loa loa infection in the anterior chamber of the eye of a 65-year-old female from rural area of Jharkhand, India, with no history of travel to endemic places but the presence of microfilaria of Loa loa in blood. Loiasis is endemic to African countries, with few sporadic cases affecting the Indian population. However, in none of the reports, microfilaremia was detected. This atypical feature in this case adds to the epidemiological variations in parasitic presentations in nonendemic regions.